Informal international lawmaking - Pauwelyn, Joost; Wessel, Ramses A.; Wouters, Jan, 1964- (Oxford : Oxford University Press, 2013)
Policy-makers, national administrations, and regulators engage in making laws without the formalities associated with treaties or customary law. This title analyses this informal lawmaking and its impact on contemporary trends in international interaction, looking at the questions of accountability and effectiveness it raises.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: International law